PERAN GURU PAI DALAM MEMBENTUK KARAKTER PESERTA DIDIK SDN 050776 TANJUNG PASIR - Halimatun Sa'diah (CV. Arsy Persada Quality, 2025)
Educate students to become intelligent human beings and also develop their personalities to have noble character. Therefore, character education is certainly important for all levels, namely from elementary school to university. In general, character education starts from an early age, if a person's character has been formed from an early age, then when they grow up they will not easily change even if temptation or seduction comes very tempting. By providing character education from an early age, it is hoped that we can produce excellent alumni, namely children of the nation who are faithful, devout, have noble character, have expertise in their fields and have character. Based on the results of observations at SD Negeri 050776 Tanjung Pasir, Prabumulih City, there are still many students who are not optimal, therefore it can be seen the description of the character of the students of SD Negeri 050776 Tanjung Pasir, therefore researchers are interested in researching the